A Content Analysis of Number Seven Advertisements from the 1970’s: The Interplay Between Beauty Advertising, Western Beauty Ideals, and Values - Denison, Holly (2016)
Previous literature regarding the interplay between beauty advertising, Western beauty ideals, and cultural values is replete with methodological issues and lacks objectivity. There are a number of reasons for this. Firstly, due to the controversies surrounding the beauty industry, it is almost exclusively studied from a critical standpoint and seldom appears in the management literature. However, the beauty industry has great significance as both a market and an influencer of cultural values. With regards to methodological issues, existing studies tend to focus exclusively on either the imagery content of an advertisement or the textual content of an advertisement. Moreover, previous research rarely examines both the dominant and subsidiary themes manifest in advertising. Accordingly, the ability of these studies to capture the richness of advertising as a communication is limited. This study was undertaken to address these research issues. More specifically, this dissertation examined the interplay between beauty advertising, Western beauty ideals, and cultural values. This was based on a content analysis of Number Seven advertisements from the 1970’s. The purpose of this study was comprised of two parts. Firstly, this study examined the dominant and subsidiary themes manifest in the Number Seven advertisements, with regards to both values and beauty types. Secondly, this study examined the congruence between the overall value and beauty themes depicted in the advertisements and the prevalent feminist values in the 1970’s. The research findings have theoretical and managerial implications for practice. Moreover, research limitations are recognized and future recommendations for research are provided.